Evaluating the Performance of Classification Algorithms on the UNSW-NB15 Dataset for Network Intrusion Detection - Putra, Zico Pratama (Jurnal Ilmiah FIFO, 2024)
Network intrusion detection is a critical aspect of cybersecurity, aiming to distinguish between normal and malicious network activities. This study evaluates the performance of various machine learning algorithms on the UNSW-NB15 dataset for binary classification of network traffic into normal and attack categories. We employed several preprocessing steps, including handling missing values, encoding categorical features, and addressing class imbalance using a mix of Synthetic Minority Over-sampling Technique (SMOTE) and undersampling. The models evaluated include k-Nearest Neighbors (k-NN), Naive Bayes, Logistic Regression, Support Vector Machines (SVM), and Neural Networks. Our experimental results show that complex models like Neural Networks and SVMs significantly outperform simpler models. The Neural Network model achieved the highest accuracy of 92%, with a precision of 91%, recall of 93%, and an F1-score of 92%. SVM also performed robustly with an accuracy of 90%. Simpler models, while less effective, still achieved respectable performance, with Logistic Regression and k-NN reaching accuracies of 88% and 85%, respectively. The study highlights the importance of comprehensive preprocessing and the implementation of advanced machine learning techniques for effective network intrusion detection. The results suggest that while complex models offer superior detection capabilities, simpler models can still be valuable in resource-constrained environments. Future research should focus on applying these models to real-world data, exploring more advanced neural network architectures, and implementing cost-sensitive learning techniques to further enhance detection performance and efficiency.